2008
DOI: 10.1007/s00425-008-0829-7
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress affects xylem differentiation of grey poplar (Populus × canescens)

Abstract: In this study the impact of salt stress on the physiology and wood structure of the salt-sensitive Populus x canescens was investigated. Two weeks of salt stress altered wood anatomy significantly. The xylem differentiation zone was reduced and the resulting vessels exhibited reduced lumina. To understand this phenomenon, ion composition, levels of corresponding transcripts and of the stress hormone ABA were analysed. With increasing sodium and chloride concentrations, a general reduction of potassium was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…3F). Comportamento similar foi observado em raízes de Populus x canescens nas quais ocorreu uma redução das camadas e do diâmetro dos elementos de vasos, à medida que aumentava o período de exposição a solos salinizados (ESCALANTE-PÉREZ et al, 2009;JUNGHANS et al, 2006). Verificou-se, também, que o incremento da concentração salina resultou em maior lignificação G. M. Melo et al das células xilemáticas e endodérmicas (FIG.…”
Section: Resultsunclassified
“…3F). Comportamento similar foi observado em raízes de Populus x canescens nas quais ocorreu uma redução das camadas e do diâmetro dos elementos de vasos, à medida que aumentava o período de exposição a solos salinizados (ESCALANTE-PÉREZ et al, 2009;JUNGHANS et al, 2006). Verificou-se, também, que o incremento da concentração salina resultou em maior lignificação G. M. Melo et al das células xilemáticas e endodérmicas (FIG.…”
Section: Resultsunclassified
“…Especially, differentiation of xylogenic cambium is a flexible developmental process that is also influenced by environmental factors (Junghans et al, 2006). Indeed, xylem differentiation zone and lumina are reduced under high salt conditions (Escalante-Pé rez et al, 2009). It is therefore likely that VNI2 transcriptional repressor activity during xylem vessel development would be compromised by the transcription activation domain that is active under high salt conditions, contributing to plant fitness for enhanced stress tolerance and leaf longevity.…”
Section: Vni2 Is a Bifunctional Transcription Factormentioning
confidence: 99%
“…Salt-stressed plants developed fewer radial cell layers in the cambial zone and narrower vessels than control trees (Escalante-Pérez et al 2009 ). Junghans et al ( 2006 ) reported that high salt concentrations reduced cambial activity and vessel diameters of P. × canescens plants.…”
Section: Salt Stressmentioning
confidence: 97%
“…The wider vessel diameters of nonstressed P. × canescens plants may be associated with higher indole-3-acetic acid (IAA) concentrations in the xylem of control plants (Junghans et al 2006 ). Salinity may also cause increased ABA synthesis and accumulation, which in turn may modulate various physiological processes related to plant hydraulics (Escalante-Pérez et al 2009 ;Shatil-Cohen et al 2011 ).…”
Section: Salt Stressmentioning
confidence: 98%